The effects of saponin from Sapindus rarak fruit on rumen microbes and performance of sheep - Amlius Thalib; Y Widiawati; H Hamid; D Suherman; M Sabrani (Jurnal Ilmu Ternak dan Veteriner, 1996)
Eighteen local sheep weighing approximately 15 kg were randomly divided into 3 treatment groups . All animals received a mixture of elephant and native grasses (50 :50) ad libitum + concentrate (0.5% of liveweight) . The treatments given were : (1) no additive, (II) addition of placebo and (III) addition of methanol-extracted Sapindus rarak fruit (MES) at level of 0.07% of liveweight. Placebo and MES were given orally every 3 days . Feeding treatments were conducted for 14 weeks . Rumen liquor of all animals were collected in the third week "and observed for rumen ecosystem and ruminal digestibility . Bodyweight gain and feed consumption were measured . The results showed that MES eliminates the protozoal population by 57% and sequently increases bacterial population by 69% when compared to control (1). Lowered protozoa population has no effect on lactic acid and total volatile fatty acids productions, and a consequence, does not change pH (Pa0.05) . However, lowered protozoa population decreased NH3-N content (P<0 .05) . Cumulative gas production resulting from substrate (rice straw) fermented by rumen liquor from sheep fed MES-added diet (III) increased by 13% when compared to control (1)). Compared to control (I), average daily gain of sheep fed MES-added diet (111) is increased by 44% with an improved efficiency by 28%.   Keywords : Saponin, protozoa, bacteria, performance of sheep